Identifying Excessive Intake of Oil and Salt to Prevent and Control Hypertension: A Latent Class Analysis - He, Lu; Yan, Yan; Wang, Yuxiao; Sun, Yudan; La, Yuanyuan; Liu, Jie; Cai, Yutong; Cao, Xi; Feng, Qilong (Frontiers in Cardiovascular Medicine, 2022)
Introduction: To identify health hazard behaviors and provide a basis for targeted management and intervention for patients with hypertension, we classified their health-related behaviors. Methods: A multi-stage random sampling method was used to conduct an on-site questionnaire survey among residents aged ≥15 years in a certain urban area of Taiyuan City, Shanxi Province, China. A latent class analysis was used to classify the lifestyle behaviors of patients with hypertension. The lifestyle behavior characteristics of different types of patients with hypertension and their awareness of hypertension were assessed. Results: The prevalence of hypertension in Taiyuan City was 19.5%. Patients with hypertension were classified into three clusters according to their lifestyle patterns: smoking and drinking (13.35%), excessive edible oil and salt intake (68.27%), and healthy behavior (18.38%). Comparing the three latent classes of lifestyle, the distribution of age, sex, marital status, and education level was different (P<0.05). The awareness of hypertension and the rate of control among the three classes were also different (P<0.05). Conclusion: The lifestyle behaviors of patients with hypertension have evident classification characteristics. Approximately two-thirds of the patients with hypertension have an excessive intake of oil and salt. Therefore, targeted and precise intervention measures should be taken to control the intake of oil and salt in this cohort.